Fish as Bioindicators: Monitoring Environmental Mercury Pollution with Aquatic Food Webs – A Mini Review - Ebadi, Abdol Ghaffar; Boufahja, Fehmi; Al Sulivany, Basim, S. A.; Selamoglu, Zeliha (International Journal of Environmental Science and Green Technology, ISSN: 3080-8693, 2025)
Mercury pollution remains a persistent concern in aquatic ecosystems due to its persistence, bioaccumulation, and toxicity. Fish, as long-lived, trophically diverse organisms, are extremely effective bioindicators of mercury pollution, providing information on spatial and temporal ecosystem pollution trends. The following mini-review consolidates current information on the utilization of fish in tracing environmental mercury, with an emphasis on mercury uptake dynamics, bioaccumulation, and biomagnification along aquatic food chains. Special attention is given to the species-specific patterns of mercury deposition, physiologic and ecological regulation of mercury retention, and regional case studies demonstrating the application of fish-based biomonitoring. Brief overview is given of analytical methods used for the determination of total mercury and methylmercury in fish tissues, as well as recent advances in stable isotope tracing and molecular biomarkers. Besides, the review also addresses the impact of mercury-contaminated fish consumption on human health, coupling environmental monitoring with public health risk assessment. Last but not least, fish are an integrative tool to assess ecosystem integrity, determine pollution sources, and support regulatory mechanisms in mercury risk management.